PEMODELAN MATEMATIKA ALIRAN UDARA PADA BRONKUS AKIBAT PENYAKIT ASMA BRONKIAL - Madinda, Diah Putri; Fatahillah, Arif; Setiawani, Susi (Kadikma, 2019)
Bronchial asthma is a disease of the narrowing of the airways located in the human bronchi. One of the factors causing this narrowing is Particulate Matter 2.5. Particulate Matter 2.5 is a kind of particle with dust that can cause narrowing of the airways. These particles are very small, ie less than 2.5 micrometer and can enter the lungs. Mathematical modeling is a way of solving problems that describe a mathematical solution in the real world. Mathematical modeling can form a mathematical model that describes the flow of air on the bronchi due to bronchial asthma according to actual conditions and important influences in them. In this study formed a mathematical model of bronchial air flow due to bronchial asthma. Mathematical models are obtained from the momentum and mass equations which are solved using the finite volume method. Keywords: Asthma, Mathematical modeling, Finite volume